Sistem Pendukung Keputusan Pemilihan Santri untuk Menjadi Kepala Pondok Menggunakan Metode ViÅ¡ekriterijumsko Kompromisno Rangiranje (VIKOR) - Muhammad Rizqi Hibatullah; Henny Dwi Bhakti; Putri Aisyiyah Rakhma Devi (Jurnal Teknika, 2022)
In the boarding school, there is still no election for the head of the boarding school chosen by several students, previously the election used the old method. The purpose of this study is to make it easier for the Islamic boarding school to choose the head of the boarding school. The flow of the first research stage is to conduct interviews with agencies that are used as objects to obtain data or information needed in research. This stage is carried out to create unfinished data which will be processed into quality data into new results and discoveries. Decision Support System is a test carried out for the accuracy of the experiment and the method so as to produce the expected information. Then determine the index value or Q on the alternative values and these values are ranked. In the ViÅ¡ekriterijumsko Kompromisno Rangiranje (VIKOR) method, the smallest value is selected and the one who is entitled to a position to become the head of the Pondok Pesantren Entrepreneur Benjeng is alternative A10 with the smallest value or 0,0.